Circulating tumor HPV DNA complements PET‐CT in guiding management after radiotherapy in HPV‐related squamous cell carcinoma of the head and neck. Issue 4 (30th September 2020) - Tanaka, Hidenori; Takemoto, Norihiko; Horie, Masafumi; Takai, Erina; Fukusumi, Takahito; Suzuki, Motoyuki; Eguchi, Hirotaka; Komukai, Sho; Tatsumi, Mitsuaki; Isohashi, Fumiaki; Ogawa, Kazuhiko; Yachida, Shinichi; et al.
Abstract: Positron emission tomography and computed tomography (PET‐CT) is widely used to assess the response to radiotherapy. However, the ability of PET‐CT to predict treatment failure in human papillomavirus (HPV)‐related squamous cell carcinoma of the head and neck (HNSCC) is unsatisfactory. We quantified circulating tumor HPV type16 DNA (ctHPV16DNA) using optimized droplet digital PCR in 35 patients with HPV16‐related HNSCC, who received radiotherapy with or without chemotherapy, and prospectively correlated ctHPV16DNA and metabolic response with treatment failure. After a median follow‐up of 21 months, ctHPV16DNA and PET‐CT had similar negative predictive values (89.7% vs 84.0%), whereas the positive predictive value was much higher in ctHPV16DNA than in PET‐CT (100% vs 50.0%). Notably, six patients who had detectable posttreatment ctHPV16DNA all had treatment failure irrespective of metabolic response, whereas none of five patients who had partial metabolic response without detectable posttreatment ctHPV16DNA had treatment failure. The risk of treatment failure was high in patients who had incomplete metabolic response with detectable posttreatment ctHPV16DNA (hazard ratio [HR], 138.8; 95% confidence interval [CI], 15.5‐3366.4; P  < .0001) and intermediate in patients who had discordant results between metabolic response and posttreatment ctHPV16DNA (HR, 4.7; 95% CI, 0.8‐36.2, P = .09) as compared with patients who had complete metabolic response without detectable posttreatment ctHPV16DNA. One‐year event‐free survival rates of each risk group were 0%, 88% (95% CI, 46‐98) and 95% (95% CI, 72‐99), respectively ( P  < .0001). In conclusion, posttreatment ctHPV16DNA complements PET‐CT and helps guide decisions managing patients with HPV16‐related HNSCC after radiotherapy. Abstract : What's new? Decisions regarding salvage surgery following radiotherapy for head and neck squamous cell carcinoma (HNSCC) are fraught with uncertainty. Post‐radiotherapy disease surveillance currently is managed with positron emission tomography and computed tomography (PET‐CT), though predictive value is exceedingly low for human papillomavirus (HPV)‐related HNSCC. This study shows that circulating tumor HPV DNA (ctHPVDNA), quantified by droplet digital PCR, complements PET‐CT in predicting post‐radiotherapy treatment failure in HPV‐related HNSCC. In particular, incomplete metabolic response with detectable post‐treatment ctHPVDNA was associated with high risk of treatment failure. Detection of ctHPVDNA after radiotherapy in HPV‐related HNSCC could help identify patients who require close follow‐up.